2020
DOI: 10.1186/s13568-020-01134-z
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of pathogenic Pseudomonas isolated from citrus in Tunisia

Abstract: The damages observed in Tunisian citrus orchards have prompted studies on the Pseudomonas spp. responsible for blast and black pit. Prospective orchards between 2015 and 2017 showed that the diseases rapidly spread geographically and to new cultivars. A screening of Pseudomonas spp. isolated from symptomatic trees revealed their wide diversity according to phylogenetic analysis of their housekeeping rpoD and cts genes. The majority of strains were affiliated to Pseudomonas syringae pv. syringae (Phylogroup PG0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 64 publications
(110 reference statements)
2
1
1
Order By: Relevance
“…The analysis of the individual genes showed that the result obtained from the individual analysis of the rpoD gene was the one that best represented the clustering results obtained by MLSA. This agrees with what was seen by Oueslati et al, who used the rpoD, 16S, and gyrB genes to study the phylogenetic relationship of Pseudomonas syringae isolates [63]. Other authors have proposed that the cts gene alone can accurately predict the phylogenetic grouping for the P. syringae group [47].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The analysis of the individual genes showed that the result obtained from the individual analysis of the rpoD gene was the one that best represented the clustering results obtained by MLSA. This agrees with what was seen by Oueslati et al, who used the rpoD, 16S, and gyrB genes to study the phylogenetic relationship of Pseudomonas syringae isolates [63]. Other authors have proposed that the cts gene alone can accurately predict the phylogenetic grouping for the P. syringae group [47].…”
Section: Discussionsupporting
confidence: 88%
“…Regarding gentamicin, the absence of resistance among the isolates studied agrees with earlier studies where it was seen that resistance to this antibiotic is not a widespread characteristic in the genus Pseudomonas [28,63]. This can be explained since, in contrast to streptomycin, gentamicin binds to multiple sites on ribosomes; thus, several mutations in bacterial chromosome would be needed to generate spontaneous mutants resistant to gentamicin [38].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although some studies have tested the efficacy of certain phages against the P. syringae complex, no study has so far reported on the isolation and characterization of phages with potential lytic activity against the citrus phytopathogenic Pseudomonas, and particularly against P. syringae pv. syringae PG02b, the most aggressive phylogroup in Tunisian citrus orchards [23,24]. In the present study, we report on the isolation and molecular characterization of the SoKa phage.…”
Section: Introductionmentioning
confidence: 85%